Intracranial aneurysm is predicted by abdominal aortic calcification index: A retrospective case-control study - Rantasalo Ville; Gunn Jarmo; Kiviniemi Tuomas; Hirvonen Jussi; Saarenpää Ilkka; Kivelev Juri; Rahi Melissa; Lassila Elli; Rinne Jaakko; Laukka Dan (Elsevier Ireland Ltd, 2022)
Background and aims
Patients with intracranial aneurysms (IA) have excess mortality for cardiovascular diseases, but little is known on whether atherosclerotic manifestations and IA coexist. We investigated abdominal aortic calcification index (ACI) association with unruptured and ruptured IAs.
Methods
This retrospective case-control study reviews all tertiary centers patients (n = 24,660) who had undergone head computed tomography angiography (CTA), magnetic resonance angiography (MRA) or digital subtraction angiography (DSA) for any reason between January 2003 and May 2018. Patients (n = 2020) with unruptured or ruptured IAs were identified, and patients with available abdominal CT were included. IA patients were matched by sex and age to controls (available abdomen CT, no IAs) in ratio of 1:3. ACI was measured from abdomen CT scans and patient records were reviewed.
Results
1720 patients (216 ruptured IA (rIA), 246 unruptured IA (UIA) and 1258 control) were included. Mean age was 62.9 ± 11.9 years and 58.2% were female. ACI (OR 1.02 per increment, 95%CI 1.01–1.03) and ACI>3 (OR 5.77, 95%CI 3.29–10.11) increased risk for rIA compared to matched controls. UIA patients' ACI was significantly higher but ACI did not increase odds for UIA compared to matched controls. History of coronary artery disease was less frequent in rIA patients. There was no calcification in aorta in 8.8% rIA and 13.6% UIA patients (matched controls 25.7% and 22.6% respectively, p < 0.01).
Conclusions
Aortic calcification is greater in rIA and UIA patients than matched controls. ACI increases risk for rIAs.